The importance of detailed context reinstatement for the production of identifiable composite faces from memory. Issue 3 (16th March 2021) - Fodarella, Cristina; Marsh, John E.; Chu, Simon; Athwal-Kooner, Palwinder; Jones, Helen S.; Skelton, Faye C.; Wood, Ellena; Jackson, Elizabeth; Frowd, Charlie D.
ABSTRACT: Memory is facilitated by reflecting upon, or revisiting, the environment in which information was encoded. We investigated these "context reinstatement" (CR) techniques to improve the effectiveness of facial composites – visual likenesses of a perpetrator's face constructed by eyewitnesses. Participant-constructors viewed a face and, after a one-day-delay, revisited (Physical CR) or recalled the environmental context (Mental/Detailed CR) before recalling the face and constructing an EvoFIT or a PRO-fit composite. Detailed CR increased correct naming of ensuing composites, but only when participant-constructors suitably encoded the environment. Detailed CR was also effective when combined with another interviewing technique (Holistic-Cognitive Interview), with focus on a target's character; it was no more effective prompting constructors to engage in greater environmental recall. Analyses indicate that the Detailed CR advantage was mediated by an increase in face recall. Results are applicable by forensic practitioners to aid eyewitness memory, thereby potentially increasing suspect identification and subsequent arrest rates.